2019
DOI: 10.5829/ije.2019.32.11b.09
|View full text |Cite
|
Sign up to set email alerts
|

Strain and Damage Sensing Property of Self-compacting Concrete Reinforced with Carbon Fibers

Abstract: A B S T R A C TPresent paper investigated the strain and damage sensing property on concrete cubes embedded with carbon fibers. Concrete cubes of dimension 150 mm have been casted with different concentration of carbon fibers to study the strain and damage sensing property under cyclic loading that can be further used for health monitoring as non-destructive testing (NDT) approach. All the specimens were tested under cyclic loading within elastic region of the sample for three cycles of loading with a maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The study revealed that this addition made the cement paste highly sensitive to its own structural damage, enabling successful crack detection. On a similar note, Arvind [33] conducted a study involving self-compacting concrete (SCC) reinforced with CNF. Their findings indicated that the damage sensing capacity of SCC increased proportionally with the CNF content, ranging from 0 to 2%.…”
Section: Fig 8 Results Of Crack Detection Testmentioning
confidence: 99%
“…The study revealed that this addition made the cement paste highly sensitive to its own structural damage, enabling successful crack detection. On a similar note, Arvind [33] conducted a study involving self-compacting concrete (SCC) reinforced with CNF. Their findings indicated that the damage sensing capacity of SCC increased proportionally with the CNF content, ranging from 0 to 2%.…”
Section: Fig 8 Results Of Crack Detection Testmentioning
confidence: 99%